Waste spunlaced facial puff derived monolithic flexible carbon framework (WCF): an ultralow-cost, recyclable and eco-friendly sorbent for oils and organic solvents. Issue 54 (2nd October 2019) - Ren, Huiru; Hao, Jingbiao; Kang, Weimin; Wang, Gang; Ju, Jingge; Li, Lei; Cheng, Bowen
Abstract : A three-dimensional carbon framework material as an excellent sorbent for oils and organic solvents was synthesized using waste spunlaced facial puff. Abstract : Due to the spunlaced effect, waste spunlaced facial puff has a high degree of fiber entanglement and an abundant three-dimensional (3D) network porous structure, which make it form a 3D carbon framework material more easily after carbonization. For the first time, the monolithic 3D carbon framework is synthesized from waste spunlaced facial puff (WCF) and used as the adsorbent for contaminants in water. The adsorption capacity of WCF for oils and organic reagents can be 34–137 times its own weight. Over five adsorption-harvesting cycles, the adsorption capacity of WCF to organic pollutants can recover up to 95% of its initial capacity. Moreover, WCF exhibits stable permeation flux and high separation efficiency in a water–heavy oil system, which is about 7714 L m −2 h −1 and higher than 99%, respectively. With a combination of waste spunlaced facial puff with monolithic 3D porous structure as a raw material, facile and green preparation process, low density, excellent hydrophobicity and lipophilicity, WCF as an adsorbent has great superiority in removal of organic pollutant solvents and environmental protection as well as other applications, such as energy storage materials, catalyst carriers, electric information, etc. Furthermore, this work would provide a new strategy for recovery use of waste spunlaced cotton materials.